Water-cooling System Design for EMUs TGA16 Traction Converter - ZOU Dangbing; RONG Zhilin; WENG Xingfang; LIU Da (机车电传动)
The composition, principle and technical parameters of TGA16 traction converter were analyzed, and the power loss of traction converter was calculated. The composition and principle for the water-cooling system of traction converter were described, the design and selection methods for the key components of the water-cooling system were provided. Finally, the water-cooling system was proved satisfying the demand of TGA16 traction converter.